2022
DOI: 10.1007/s00248-022-02092-8
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Communities Are More Sensitive to the Simulated Environmental Changes than Bacterial Communities in a Subtropical Forest: the Single and Interactive Effects of Nitrogen Addition and Precipitation Seasonality Change

Abstract: Increased nitrogen (N) deposition and changes in precipitation seasonality can greatly impact soil microbial communities in tropical/subtropical forests. Although knowledge about the effects of a single factor on soil microbial communities is growing rapidly, little is understood about the interactive effects of these two environmental change factors. In this study, we investigated the responses of soil bacterial and fungal communities to the simulated environmental changes (nitrogen addition, precipitation se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Thus, the persistent increase in soil inorganic nitrogen led to the highest R m N and R NN in the last investigation. However, a persistent N addition could decrease the soil pH and depress microbial activities [61][62][63], which could subsequently decrease R m N and R NN . Although the pH was 10.43 beneath the shrubs and 10.08 in the interplant at the beginning of N treatment, N addition did not lead to soil acidification.…”
Section: Effects Of N Addition On Soil Net N Mineralization and Nitri...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the persistent increase in soil inorganic nitrogen led to the highest R m N and R NN in the last investigation. However, a persistent N addition could decrease the soil pH and depress microbial activities [61][62][63], which could subsequently decrease R m N and R NN . Although the pH was 10.43 beneath the shrubs and 10.08 in the interplant at the beginning of N treatment, N addition did not lead to soil acidification.…”
Section: Effects Of N Addition On Soil Net N Mineralization and Nitri...mentioning
confidence: 99%
“…More importantly, increased C mic :N mic and F:B suggested that N addition had a preference for promoting fungal growth. Given that the fungal hyphae can absorb soil nitrogen, fungi can better avoid N accumulation relative to bacteria [63,64], and the variation in the microbial community composition might be responsible for the different changes of R CM with R m N and R NN .…”
Section: Effects Of N Addition On Soil C Mineralizationmentioning
confidence: 99%
“…N addition has been reported to reduce the soil bacterial diversity, with significant correlation with physicochemical properties, and it also leads to increase relative abundances of Proteobacteria and Actinobacteria ( Dai et al, 2018 ; Zhang X. et al, 2022 ). In addition, N application significantly enhances the fungal diversity and relative abundances of certain fungi, showing significant correlations with soil available nutrients, but it does not appear to impact fungal community composition in tropical/subtropical forests, suggesting that N input primarily influences microbial diversity and relative abundance by modulating soil physicochemical properties ( He et al, 2021 , 2022 ; Zhang X. et al, 2022 ). At the same time, N input influences the contents of proteins, amino acids, nucleic acids, and hormones containing N elements, all of which play pivotal roles in various metabolic processes in soil.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal precipitation significantly increases soil rare bacteria and dominant fungi ( He et al, 2017 ; Zhao et al, 2017 ). Additionally, the composition and function of soil microbial communities are impacted by the availability of soil water ( Brockett et al, 2012 ; Diaz-Pereira et al, 2019 ); however, the direction and magnitude of soil microbial community composition and function following changes in precipitation remain uncertain ( Zhao et al, 2017 ; He et al, 2022 ). Furthermore, there is a lack of studies investigating the soil microbial community network structure in response to precipitation change ( He et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%